Clostridium strain FAM25158, a unique endospore-forming bacterium related to Clostridium tyrobutyricum and isolated from Emmental cheese shows low tolerance to salt - Prinčič, Lucija; Burtscher, Johanna; Sacken, Paul; Krajnc, Tina; Domig, Konrad J. (Frontiers in Microbiology, 2024)
The genus Clostridium is a large and diverse group of species that can cause food spoilage, including late blowing defect (LBD) in cheese. In this study, we investigated the taxonomic status of strain FAM25158 isolated from Emmental cheese with LBD using a polyphasic taxonomic and comparative genomic approach. A 16S rRNA gene sequence phylogeny suggested affiliation to the Clostridium sensu stricto cluster, with Clostridium tyrobutyricum DSM 2637T being the closest related type strain (99.16% sequence similarity). Average Nucleotide Identity (ANI) analysis revealed that strain FAM25158 is at the species threshold with C. tyrobutyricum, with ANI values ranging from 94.70 to 95.26%, while the digital DNA-DNA hybridization values were below the recommended threshold, suggesting that FAM25158 is significantly different from C. tyrobutyricum at the genomic level. Moreover, comparative genomic analysis between FAM25158 and its four closest C. tyrobutyricum relatives revealed a diversity of metabolic pathways, with FAM25158 differing from other C. tyrobutyricum strains by the presence of genes such as scrA, srcB, and scrK, responsible for sucrose utilization, and the absence of many important functional genes associated with cold and osmolality adaptation, which was further supported by phenotypic analyses. Surprisingly, strain FAM25158 exhibited unique physiologic traits, such as an optimal growth temperature of 30°C, in contrast to its closest relatives, C. tyrobutyricum species with an optimal growth temperature of 37°C. Additionally, the growth of FAM25158 was inhibited at NaCl concentrations higher than 0.5%, a remarkable observation considering its origin from cheese. While the results of this study provide novel information on the genetic content of strain FAM25158, the relationship between its genetic content and the observed phenotype remains a topic requiring further investigation.